The Irresponsible Personality - Wadhwani, Gyandas G.; Bhatia, Saloni (Homœopathic Links, 2014)
Rheumatoid arthritis is a chronic, systemic, inflammatory, autoimmune disorder of multifactorial origin. Its multisystem involvement requires therapeutic intervention of specialists in conventional medicine from various departments. Homeopathy views any disease as a disturbance in the dynamic continuum of the human organism. It therefore requires a thorough elicitation of each personʼs individual patho-bio-graphical personality for therapeutic intervention. A diagnosed case of rheumatoid arthritis was treated with individualized homeopathic drug therapy on the basis of pathological general “irresponsibility” and followed up for a period of three years. Effective disease remission was maintained for two years without the need for conventional medication, which was confirmed by serological markers and DAS28 score.
Keywords: Rheumatoid arthritis; Irresponsible personality; Boger; Pathological general; Thymus gland extract; Sarcodes